Screening of the Acaricidal Activity of Essential Oils against Panonychus citri (McGregor) (Acari: Tetranychidae) - Yijing Zhu; Taoqi Wu; Yongjian Xie; Yixuan Wu; Jianyu Deng; Lidong Cao; Zhijun Zhang; Qiong Rao (Agronomy, 2023)
The citrus red mite, Panonychus citri (McGregor), is an important pest of citrus in China, where pesticides are commonly used in citrus orchards. In order to reduce the use of chemical pesticides against P. citri and the development of resistance, the screening of biological control agents has attracted the attention of students. In this study, seven plant essential oils with high toxicity were selected from 40 plant essential oils by the leaf-dip bioassay, including plant essential oils of lemongrass, patchouli, juniper berry, sage, clove, frankincense, and citrus. The LC50 after 72 h treatment were 3.198 μL/mL, 8.312 μL/mL, 3.244 μL/mL, 6.701 μL/mL, 8.350 μL/mL, 21.953 μL/mL, and 8.788 μL/mL, respectively. According to the LT50, the essential oils’ acute toxicity to P. citri from high to low were lemongrass, juniper berry, patchouli, citrus, sage, vetiver, and frankincense essential oils. In general, lemongrass and juniper berry essential oils have the best acaricidal effect and have high application value for the biological control of P. citri, which provides a basis for the development of botanical acaricides.